Impact of ultraviolet B radiation applications on some secondary metabolites in thyme (Thymus vulgaris L.) - Ramírez-Alvarado, Rafael Andrés; Herrera-Arévalo, Aníbal Orlando; Ortiz-Rojas, Yamid; Pérez-Rodríguez, Claudia Patricia (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
The impact of ultraviolet radiation B (UV-B) applications on the production of secondary metabolites, such as phenols, flavonoids and anthocyanins, in thyme plants was studied. The stems, leaves and flowers were subjected to an experiment design that had a 4´2 factorial arrangement, evaluating: dose UV-B radiation (0.05 and 0.075 Wh m-2), sampling points (75 days after transplanting [cut-off point] and 92 days after transplanting [full flowering] according to the BBCH scale), adaptation time (24 and 49 hours) and extraction matrices of plant material (fresh and dried). The experiment unit corresponded to matrices from Thymus vulgaris L. (C.N. thyme) plants. Ten extractions were done per treatment, and a chemical analysis test were performed in triplicate. The extraction was done with a modified Randall method. The results showed that the application of UV-B radiation at a dose of 0.075 Wh m-2 increased the concentration of secondary metabolites of interest. The compounds that showed a better response to treatment were phenols and anthocyanins.